Development of Biology Teaching Modules on Biodiversity Material Based on Regional Potential to Improve Literacy Skills of Grade X Students of SMA Negeri 1 Tenggarong - Lasih; Vandalita M. M. Rambitan; Akhmad; Herliani; Elsje Theodora Maasawet; Daniel (Postgraduate, University of Mataram, 2025)
The purpose of this study was to determine the analysis of teacher and student needs for teaching modules based on regional potential, module validity, level of practicality, and effectiveness of the module in improving students' literacy skills. This study is a development research. Data were analyzed using qualitative and quantitative methods. Qualitative descriptive analysis was used to analyze data on needs, validity, and practicality of the module, while quantitative analysis was used to test the effectiveness of the module. The results of the needs analysis showed that teachers needed modules that were relevant to the local context, and students needed interesting and easy-to-understand learning media. Expert validation showed that the module had a validity index of 97.73% with a very valid category. The practicality level of the module reached 78% with a practical category. Effectiveness testing using the independent sample t-test produced a sig value. (2-tailed) of 0.000 (<0.05), which shows that the module is effective in improving students' literacy skills. The conclusion of this study is that the regional potential-based teaching module is valid, practical, and effective in improving students' literacy skills in biodiversity material.